Update on eating disorders: current perspectives on avoidant/restrictive food intake disorder in children and youth - Norris M; Spettigue W; Katzman D (Neuropsychiatric Disease and Treatment)
Mark L Norris,1 Wendy J Spettigue,2 Debra K Katzman3 1Division of Adolescent Medicine, Department of Pediatrics, Children’s Hospital of Eastern Ontario, University of Ottawa, Ottawa, ON, Canada; 2Department of Psychiatry, Children’s Hospital of Eastern Ontario, University of Ottawa, Ottawa, ON, Canada; 3Division of Adolescent Medicine, Department of Pediatrics, Hospital for Sick Children, University of Toronto, Toronto, ON, Canada Abstract: Avoidant/restrictive food intake disorder (ARFID) is a new eating disorder diagnosis that was introduced in the Diagnostic and Statistical Manual of Mental Disorders (DSM) fifth edition. The fourth edition of the DSM had failed to adequately capture a cohort of children, adolescents, and adults who are unable to meet appropriate nutritional and/or energy needs, for reasons other than drive for thinness, leading to significant medical and/or psychological sequelae. With the introduction of ARFID, researchers are now starting to better understand the presentation, clinical characteristics, and complexities of this disorder. This article outlines the diagnostic criteria for ARFID with specific focus on children and youth. A case example of a patient with ARFID, factors that differentiate ARFID from picky eating, and the estimated prevalence in pediatric populations are discussed, as well as clinical and treatment challenges that impact health care providers providing treatment for patients. Keywords: avoidant/restrictive food intake disorder, ARFID, eating disorder, picky eating, prevalence, treatment